From Persepolis to Jerusalem: A Reevaluation of Old Persian-Hebrew Contact in the Achaemenid Period - Wilson-Wright, Aren M. (Vetus Testamentum, 2015)
This paper examines the effects and mechanisms of Old Persian contact on Biblical Hebrew. I first reevaluate the number and distribution of Old Persian loanwords in the Hebrew Bible. Then I demonstrate that there was direct contact between speakers of Old Persian and speakers of Hebrew in the Achaemenid period beginning under Artaxerxes i, before proposing the existence of two Old Persian calques in Biblical Hebrew. The distribution of these Old Persian loanwords and calques strengthens the case for distinguishing between Late Biblical Hebrew and Classical Biblical Hebrew on linguistic grounds. With one exception, these features cluster in well-known Late Biblical Hebrew texts.